Trajectories of Depressive Symptoms Among Older Adults and in Adults With Hip Fracture: Analysis From the English Longitudinal Study of Ageing. Issue 12 (8th September 2022) - Milton-Cole, Rhian; Ayis, Salma; O'Connell, Matthew D L; Smith, Toby; Sheehan, Katie Jane
Abstract: Background: This study aimed to determine trajectories of depressive symptoms among older adults in England, overall and for those with hip fracture. The study aimed to explore the differential characteristics of each trajectory identified. Methods: Analysis of adults aged 60 years or more ( n = 7 050), including a hip fracture subgroup ( n = 384), from the English Longitudinal Study of Ageing. Latent class growth mixture modeling was completed. Depressive symptom prevalence was estimated at baseline. Chi-square tests were completed to compare baseline characteristics across trajectories. Results: Three trajectories of depressive symptoms (no, mild, and moderate-severe) were identified overall and for those with hip fracture. The moderate-severe trajectory comprised 13.7% and 7% of participants for overall and hip fracture populations, respectively. The proportion of participants with depressive symptoms in the moderate-severe trajectory was 65.4% and 85.2% for overall and hip fracture populations, respectively. Depressive symptoms were stable over time, with a weak trend toward increasing severity for the moderate-severe symptom trajectory. Participants in the moderate-severe symptom trajectory were older, more likely to be female, live alone, and had worse health measures than other trajectories ( p < .001). Conclusions: Older adults, and those with hip fracture, follow one of the 3 trajectories of depressive symptoms that are broadly stable over time. Depressive symptoms' prevalence was higher for those with hip fracture and, when present, the symptoms were more severe than the overall population. Results suggest a role of factors including age, gender, and marital status in depressive symptom trajectories.